Selayang Pandang Tafsir Liberal di Indonesia - Eni Zulaiha; Restu Ashari Putra; Rizal Abdul Gani (UIN Sunan Gunung Djati Bandung, 2021)
Understanding the holy book of the Koran, undergoes continuous changes, especially in terms of the interpretation of the holy text. Recently, the discourse of liberal interpretation has become something that deserves attention because it is considered capable of providing solutions to the problems of the modern era and raises many pros and cons. Several Muslim figures have even put forward a new offer to understand Islam liberally. This study intends to parse the background of the liberal interpretation in Indonesia and what methods it uses.